New Discoveries and Ambiguities of Nrf2 and ATF3 Signaling in Environmental Arsenic-Induced Carcinogenesis - Zhuoyue Bi; Yao Fu; Priya Wadgaonkar; Yiran Qiu; Bandar Almutairy; Wenxuan Zhang; Akimasa Seno; Chitra Thakur; Fei Chen (MDPI AG, 2021)
Environment exposure to arsenic had been linked to increased incidents of human cancers. In cellular and animal experimental systems, arsenic has been shown to be highly capable of activating several signaling pathways that play critical roles in cell growth regulation, malignant transformation and the stemness of cancer stem-like cells. Emerging evidence indicates certain oncogenic properties of the Nrf2 transcription factor that can be activated by arsenic and many other environmental hazards. In human bronchial epithelial cells, our most recent data suggested that arsenic-activated Nrf2 signaling fosters metabolic reprogramming of the cells through shifting mitochondrial TCA cycle to cytosolic glycolysis, and some of the metabolites in glycolysis shunt the hexosamine biosynthesis and serine-glycine pathways important for the energy metabolism of the cancer cells. In the current report, we further demonstrated direct regulation of oncogenic signals by arsenic-activated Nrf2 and connection of Nrf2 with ATF3 stress transcription factor. Meanwhile, we also highlighted some unanswered questions on the molecular characteristics of the Nrf2 protein, which warrants further collaborative efforts among scientists for understanding the important role of Nrf2 in human cancers either associated or not to environmental arsenic exposure.